Pan-cancer analysis and experimental verification of its roles and clinical significance of SLC2A3 in kidney renal clear cell carcinoma - Lyu, Zhaojie; Zhang, Xueqi; Yuan, Haichao; Yang, Qingshan; Yang, Yu; Zhao, Zhengping; Wang, Guangsuo; Bi, Liangkuan (Frontiers in Immunology, 2025)
BackgroundSolute carrier family 2 member 3 (SLC2A3), a key glucose transporter, has been implicated in tumor metabolism and immune regulation, but its specific role in kidney renal clear cell carcinoma (KIRC) remains largely unclear.MethodsWe conducted a comprehensive pan-cancer analysis of SLC2A3 using publicly available datasets. Its associations with patient prognosis, genomic heterogeneity, stemness features, immune-related genes, and immune cell infiltration were systematically explored. Functional enrichment and gene set enrichment analyses (GSEA) were conducted to explore the potential biological mechanisms in KIRC. Additionally, in vitro experiments using HK-2 and 786-O cell lines were carried out to validate the functional effects of SLC2A3.ResultsSLC2A3 expression was altered in multiple cancers, being upregulated in eight tumor types and downregulated in twenty. Elevated SLC2A3 levels were associated with poorer survival in several malignancies. SLC2A3 expression is broadly positively correlated with immune checkpoints, modulators, and several immune cells in most cancers, but shows a negative association in TGCT. In KIRC, differential expression and enrichment analyses suggested involvement of SLC2A3 in hormone regulation, extracellular matrix remodeling, complement activation, and steroid metabolism. GSEA further demonstrated significant enrichment of gene sets involved in key pro-tumorigenic pathways. Functional assays demonstrated that silencing SLC2A3 markedly inhibited cell proliferation and migration in both HK-2 and 786-O cells.ConclusionsCollectively, our data imply that SLC2A3 serves as an oncogenic driver in multiple cancers, contributing to KIRC progression via the enhancement of pro-tumorigenic pathways.